Disease-Suppressive Soils Induce Systemic Resistance in Arabidopsis thaliana Against Pseudomonas syringae pv. tomato - David M. Weller; Johan A. van Pelt; Linda S. Thomashow; Dmitri V. Mavrodi; Olga V. Mavrodi; Corné M. J. Pieterse; Peter A. H. M. Bakker (PhytoFrontiers)
Arabidopsis thaliana accession Col-0 seedlings were transferred into an autoclaved soil/sand mixture amended with either 10 or 20% (wt/wt) soil from fields in Washington State that are suppressive to take-all or Rhizoctonia root rot of wheat. Three weeks after transplanting, these plants had population sizes of 2,4-diacetylphloroglucinol (DAPG) or phenazine-1-carboxylic acid (PCA)-producing pseudomonads of greater than 5 × 105 colony forming units per gram fresh weight of root with rhizosphere soil. When the plants were challenge-inoculated with Pseudomonas syringae pv. tomato DC3000, both soils induced systemic resistance in the leaves against bacterial speck to a level similar to that induced by P. simiae WCS417r, P. fluorescens Q2-87 (DAPG+), P. brassicacearum Q8r1-96 and L5.1-96 (both DAPG+), and P. synxantha 2-79 (PCA+). Pasteurization of the soils before adding them into the soil/sand mixture eliminated DAPG- and PCA-producing pseudomonads from the Arabidopsis rhizosphere and significantly reduced induced systemic resistance activity. However, populations of total culturable aerobic bacteria were similar in the rhizosphere of plants grown in soil/sand mixes amended with untreated or pasteurized suppressive soils. This is the first report of induction of systemic resistance in Arabidopsis by take-all and Rhizoctonia-suppressive soils and the ability of PCA-producing P. synxantha 2-79 to induce resistance. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2024.